Biodegradable Geomeshes for Rainsplash Erosion Control (Journal of Fiber Bioengineering and Informatics, 2018)
Geomeshes can be employed to control erosion in conjunction with revegetation efforts, supplying seedbed protection from rainsplash erosion. In this study, jute and coir geomeshes were tested for erosion control performance under simulated rainfall conditions and germination using Shiwalik region soil. The performance of coir and jute geomeshes for rain splash erosion control were tested based on ASTM-D-7101 using a bench-sale setup with some modifications. Germination tests were performed according to ASTM-D-7322. Rain splash erosion control tests were carried out on three different slope angles of 15○, 30○ and 45○. Jute geomeshes resulted in the improvement of erosion control and soil stability than that of Coir. Also, the erosion control performance of geomeshes was observed to be influenced by the angle of soil slope. The objective of this study is to assess the performance capacities of biodegradable geomeshes that are commonly used for slope erosion control and vegetation establishment.